Upaya Penghapusan Kekerasan Seksual Melalui Implementasi Program Pemberdayaan Perempuan - Naufal Asyiri Banuarli; Ariana Ariana; Nur Alfiyani; Achmad Zulfikar (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
The role is a dynamic aspect, where the role is carried out based on the position/position attached, so when someone has carried out his function in accordance with the inherent status in himself, then he is said to have carried out a role. The role is more emphasis on community expectations of individuals, where the community expects the individual to be able to change the social order of the role he does. The role can certainly be done by everyone without exception, including the role of women leaders in fighting for women's interests. The intended role in this research is the efforts of female leaders in supporting efforts to eliminate sexual violence. This research was conducted in Makassar City. The method used is descriptive method with a qualitative approach. The technique used in data collection is through in-depth interviews with several informants as well as from other sources related to this research.The results showed that in supporting efforts to eradicate sexual violence, women leaders in Makassar had made efforts such as the Women's Change House (RPP) program, the Anti Sexual Violence campaign, Mother's School, and Parenting Education. While the program that will be carried out by female leaders is by holding a Mother School program. Abstrak Peran merupakan suatu aspek dinamis, dimana peran dilakukan berdasarkan posisi/ jabatan yang melekat, jadi ketika seseorang telah menjalankan fungsinya sesuai dengan status yang melekat dalam dirinya, maka ia dikatakan telah menjalankan suatu peranan. Peran lebih menekankan kepada pengharapan masyarakat terhadap individu, dimana masyarakat mengharapkan individu tersebut mampu merubah tatanan sosial atas peran yang dilakukannya. Peran tentu dapat dilakukan semua orang tanpa terkecuali, termasuk peran tokoh perempuan dalam memperjuangkan kepentingan perempuan. Peran yang dimaksudkan dalam penelitian ini yaitu upaya para tokoh perempuan dalam mendukung upaya penghapusan kekerasan seksual. Penelitian ini dilaksanakan di Kota Makassar. Metode yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Teknik yang digunakan dalam pengumpulan data yakni melalui proses wawancara mendalam (indepht interview) kepada beberapa informan serta dari sumber-sumber lain yang berhubungan dengan penelitian ini. Hasil penelitian menunjukkan bahwa dalam mendukung upaya penghapusan kekerasan seksual, para tokoh perempuan di kota Makassar telah melakukan upaya seperti program Rumah Perubahan Perempuan (RPP), kampanye Anti Kekerasan Seksual, Sekolah Ibu, dan Parenting Education. Sedangkan program yang akan dilakukan para tokoh perempuan yaitu dengan mengadakan program Sekolah Ibu.